Transient ornaments. A few projects for the improvement and embellishment of the Amsterdam municipal theatre on Keizersgracht, 1765-1772 (Bulletin KNOB, 2008)
Between 1765 and 1772 refurbishment work was carried out to the building and auditorium of the Amsterdam municipal theatre. Several building engineers were involved, among whom the director general of the Amsterdam building department Cornelis Rauws (1736-1772) and the regular carpenter of the municipal theatre Jan Smit (1726-1807), who advised the town councillors and made the required designs and plans. It appears from the minutes of the ordinary treasurers, who supervised the refurbishments on behalf of the town council, that in 1770 the young carpenter/architect Abraham van der Hart also made designs for the auditorium on the instructions of the governors of the theatre. His involvement proves that, although he was still referred to as 'son of the carpenter Van der Hart', in 1770 Van der Hart's exceptional qualities as an architect had already been noticed in the circles of the town governors. However, Van der Hart's involvement in the project was short-lived. The town council refused to hire an external architect, because the services of director general Rauws could be made use of free of charge.In this article the refurbishment work to the theatre in the sixties and seventies of the eighteenth century is discussed, with special attention to the design of Van der Hart. His commissioners did not only have the ambition to embellish and modernize the auditorium, but also to express the hierarchy of the various seats better. Van der Hart proved to be capable of finding better solutions to this problem than his colleagues. For that reason his designs had an enduring effect on the further decision process. Eventually, hardly any of the ambitions mentioned were fulfilled. The decision process had a certain ad-hoc character: new requirements set to the building programme by the governors or problems detected in it, were each time responded to, instead of drawing up a coherent plan. In 1771 the changes that had been carried through were even partly reversed again, because they had deteriorated the practical suitability of the auditorium. Consequently. On 11 May 1772 the theatre building was lost in a fire.